Investigation of the Catalytic Activity of the Middlings of High-Magnesian Siderites Processing - Smirnov, Andrey N.; Sysoev, Viktor I.; Krylova, Svetlana A. (Recent Patents on Materials Science, 2017)
Background: The development of resource and energy effective schemes for processing natural raw materials attracts increasing attention in the last decades. The scheme of the integrated processing of natural high-magnesian siderites (res. of 1 billion tonnes) developed and patented by our team allows obtaining several end products, the main of which are low-magnesian iron ore concentrate (Fetotal ≥ 58-60%, MgO ≤ 6-8%) and high-purity magnesia (MgO ≥ 98%). The middlings of processing high-magnesian siderites accordingly to this technology were found to be catalytically active in several well known reactions. Objective: So the objective of this research is to test the catalytic possibilities of the middlings of high-magnesian siderites processing in the water gas shift reaction and in the process of coal gasification by carbon dioxide. Method: The results of the laboratory experiments on the determination of the catalytic activity of the investigated material are presented in the article. Phase composition was determined by electron microscopy and X-Ray diffraction, chemical composition - by X-ray fluorescence and gas chromatography, specific surface - by the low temperature nitrogen adsorption method (BET method). Results and Conclusions: The middlings of high-magnesian siderites processing exhibit significant catalytic activity in the processes of coal gasification (conversion rate is 3-5 times higher in comparison with non-catalytic process) in the water gas shift reaction (the catalyst allows obtaining full conversion at the reactant load of up to 4000 h-1). The results of the research can be used in the realization of the principles of integrated high-magnesian siderites processing, including the possibility of obtaining an inexpensive catalyst for large-scale production.
Keywords: iron-magnesian oxide catalyst